PENGARUH LIKUIDITAS, STRUKTUR MODAL, UKURAN PERUSAHAAN DAN RISIKO OPERASIONAL PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2018-2020 - Gunawan, Calvin; Sudarsi, Sri; Aini, Nur (Faculty of Economic and Business Universitas STIKUBANK, 2022)
This study aims to analyze the effect of liquidity, capital structure, firm size, and operational risk on the company's financial performance. The population of manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Sampling used the purposive sampling method so as to produce 123 manufacturing companies that matched the criteria. Analysis of the data in this study using multiple linear regression. The results of the study prove that liquidity has no effect on the company's performance, capital structure has a positive and significant effect on the company's performance, the size of the company has a positive and significant effect on the company's performance, the company's operational risk has a negative and insignificant effect on the company's performance